The Ins and Outs of Involuntary Part-time Employment - Daniel Borowczyk-Martins; Etienne Lalé (Copenhagen Business School (CBS), Department of Economics, 2018)
We develop an adjustment procedure to construct U.S. monthly time series of involuntary part-time employment stocks and flows from 1976 until today. Armed with these new data, we provide a comprehensive account of the dynamics of involuntary part-time work. Transitions from full-time to involuntary part-time employment dominate this dynamics, spiking up at recessions' onsets and persisting well into recovery periods. On the other hand, weaknesses in job creation contribute little to these fluctuations. Our data and findings are relevant to inform a broader assessment of labor market performance and to develop models of cyclical labor adjustment.
hdl:10398/9671
Keywords: E24; E32; J21; 330; Involuntary part-time employment; Unemployment; Labor market flows; Business cycles